Study of modified PEDOT:PSS for tuning the optical properties of its conductive thin films - Singh, Vinamrita (H. : ĐHQGHN, 2020)
The present work focuses on studying the optical properties of the pristine PEDOT:PSS and the PEDOT:PSS modified with de-ionized water, ethylene glycol and MWCNT. The effect of various additives on the absorption, the refractive index, and the dielectric constant has been inspected. The refractive index dispersion has been analyzed using the single oscillator model developed by Wemple and DiDomenico. The optical constants, such as the dispersion energy, the single oscillator energy, the average oscillator strength, the average interband oscillator strength, the long wavelength refractive index, and the plasma resonance frequency have been determined. The energy bandgap was found reduced with the addition of EG and MWCNT representing a red shift and a conformational change in the PEDOT:PSS from a benzoid to a quinoid structure. The UV-visible absorption spectrum indicates the creation of free charges. The increase in the refractive index with doping suggests the formation of localized energy states within the energy bandgap. These localized states act as recombination centers and increase the low energy electronic transitions. The dielectric constant was also found increased in the modified samples, exhibiting advantages for the formation of conducting thin films. A phase segregated morphology was obtained for the solvent treated PEDOT:PSS, and the MWCNTs were observed to be uniformly distributed throughout the polymer. Furthermore, the optical conductivity has been calculated to give comprehensive information about material properties and their systematic selection for desired applications.